Pengelolaan Sumber Daya Manusia Efektif di Lembaga Pendidikan Islam - Endang Sih Pujiharti (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
Islamic Education Institutions are one of the platforms to realize expectations and goals in Islamic education. To prepare a generation of quality in welcoming and becoming agents of development in the era of globalization, Islamic educational institutions are demanded to be able to improve the quality of human diversity. This will be achieved if the quality of Islamic educational institutions can also be improved. Human resources are one of the most important factors in Islamic educational institutions, because human resource factors are another driving force for resources that determine the quality of Islamic education. The results of education in Islamic Education Institutions will be quality if supported by management / management of quality human resources as well. This is absolutely necessary to achieve maximum results. No matter how advanced the technology is, human factors still play a very important role for the success of an institution including Islamic educational institutions. In Islam, humans are al-insan, al-basyar, al-nas. Whereas effective management of human resources in Islamic education institutions includes the processes of planning, procurement, training and development, assessment of work performance and compensation, and maintenance of work relations.